Adaptação e avaliação de cenário de simulação clínica para manejo da hemorragia pós-parto - Lima, Adriana Moreno de (2023)
This study aimed to adapt and evaluate a clinical simulation scenario in the management of postpartum hemorrhage. This is a methodological study, in which the adaptation and evaluation of an existing scenario on the subject was carried out with the application of the simulation to the target audience and expert judges on the subject. The sample consisted of 22 judges and 22 nurses comprising the target audience. The inclusion criteria of the judges were: being a nurse who works in the care of parturients and/or puerperal women or a specialist in clinical simulation and who fulfills Fehring's criteria; and the exclusion criteria: presenting a physical or mental state of health that would make the evaluation of the clinical simulation self-declared by the participant unfeasible. The inclusion criteria of the target public were to be graduated in Nursing and work in the field of Obstetrics; the exclusion criterion was to present a physical or mental state of health that would make participation in the clinical simulation unfeasible, self declared by the participant. Data collection took place from August to October 2022 and consisted of data about the sociodemographic profile of the target audience and the judges; application of the assessment instruments for the target audience and the judges adapted from Andrade et al., 2019. The instrument for evaluating content and appearance by the judges and evaluating appearance by the target audience was also completed by the research participants. Data were compiled and analyzed using the statistical program Statistical Package for the Social Sciences, version 21.0. The clinical simulation scenario followed Jeffries' theoretical framework, consisting of the elements: prebriefing, simulation objectives, participants, scenario and debriefing process, as well as being based on the guides of the International Nursing Association for Clinical Simulation in Learning (INACSL). The project was submitted to the Research Ethics Committee at Maternidade Escola Assis Chateaubriand and approved through the Plataforma Brasil. As for the results of the work, changes were made to the scenario, with the methodological division of the scenario into three sections: scenario adaptation planning, scenario and scenario script. The insertion of tranexamic acid was one of the updated points in drug therapy. As for sociodemographic data, it was found that the public was mostly female, specialists, average of 29.8 years, average of working time in the professional area of 6.8 years, all with experience in women's health care, most with publications in the area of obstetrics and/or clinical simulation and who has already taught and/or participated in training on the subject. As for the judges, most of them were female, doctors, with an average age of 39.4 years, average of working time on the subject of 17.5 years, with experience in women's health care, all of whom had experience teaching in women's health, most had publications in the area of obstetrics and/or clinical simulation and had already given and/or participated in training on the subject. As for the evaluation instrument used by the target audience, 95.8% of the judges agreed that the writing was considered clear and objective, that the text is interesting, that the appearance of the scenario is simple and clear and that the scenario invites/incites changes of behavior and attitude during assistance. The items that had the highest disagreement value among the target audience were whether the vocabulary is accessible, whether the scenario is appropriate for the profile of undergraduate students and whether the scenario proposes knowledge for students. With regard to the judges' assessment instrument, the following items had 100% agreement: “the content facilitates critical thinking”; “there is a logical sequence of proposed content” and “the purpose of the scenario invites and/or instigates changes in behavior and attitude of students towards postpartum hemorrhage”. One judge stated that he disagreed with the item that says that the theme approaches key aspects that should be reinforced. The reliability for the overall appearance assessment instrument resulted in a Cronbach's alpha value of 0.841, which indicates that there is good internal consistency, and the Intraclass Correlation Coefficient (ICC) was 0.844, which indicates good reliability. As for the content and appearance instrument, the overall reliability of the instrument using the Cronbach alpha test was 0.872, resulting in good internal consistency. As for the ICC test, the result of average measurements was 0.872, which means good overall reliability. The Concordance Index (CI) was also calculated for the instrument items of the target audience and judges. As for the CI of the target audience, 11 items had 100% agreement and the remaining items (5) had 95.8% agreement. Regarding the judges' instrument, 17 items had 100% agreement and 5 items had 95.4% agreement. The calculation of the Binominal Test for the content and appearance assessment instrument, to verify the agreement between the specialists regarding the adequacy and use of the scenario, resulted in all the instrument item values above 0.85, which indicates the agreement between the judges for the use of the scenario. The scenario was considered suitable for use by the judges and considerations and adjustments suggested by the experts were made in the evaluation instrument.